Spray-dried whey protein concentrate-iron complex : preparation and physicochemical characterization - Banjare, Indrajeet Singh (Array, 2019)
Poor absorption of iron from food and oral iron formulations results in extensive use of high-dose oral iron, which is not tolerated. Disposal of whey, a byproduct of the cheese industry, causes environmental pollution. Whey proteins have the ability to bind significant amount of iron, thereby reducing its chemical reactivity and incompatibility with other components in foods. To make iron compatible with food, it was complexed with whey protein concentrate (WPC). After complexation, centrifugation and ultrafiltration techniques were utilised to eliminate the insoluble and free iron from the solution. To enable the availability of whey protein concentrate–iron (WPC–Fe) complex in the powder form, spray drying technique was used. Optimized spray drying conditions used for the preparation were: inlet temperature 180 °C, flow rate 2.66 mL/min and solution of total solids 15 %. The complex was observed to be stable under different processing conditions.